Studio project on the sculpture entitled retrospection and prodigy series / Mohd Khairi Baharom and Siti Ermi Syahira Abdul Jamil - Baharom, Mohd Khairi; Abdul Jamil, Siti Ermi Syahira (Universiti Teknologi MARA, Perak, 2021)
An artwork creation requires a particular process which involves knowledge, creativity and skill. The process demands the artist’s comprehension of the work’s issue that is usually incorporated in the artwork. This article discusses the process of sculpture that applies via the studio-based research method of which the study has integrated data investigation, progression of idea, fabrication of artwork and art criticism. This study determined a series of sculptures titled Retrospection and Prodigy made by Mohd Khairi Baharom (2012) which practiced the studio-based research method. To incorporate the critical issue in the sculpture, the studio project investigated the sculptor’s center of discussion that has been used in the phenomenological study approach. The sculptor’s childhood memory lives in rural areas with limited accessibility causing the expansion of his imagination and craft skills. This matter has motivated him to use his childhood reminiscence for the aesthetic content in the sculpture. The sculpture process involved several phases of studio projects such as data compilation, concept and form development, and artwork fabrication. The additional data of sculpture criticism has also been included in the article for better interpretation.